Unveiling the financial landscape: analyzing profitability, productivity, and efficiency of banks in an emerging economy using the CAMELS framework and panel analysis - Shakeb Akhtar; Shujaat Naeem Azmi; Parvez Alam Khan; Ahmad Ali Jan; Zahin Ansari (Cogent Business & Management, 2024)
This study examines the banking sector's performance by conducting a two-step analysis using balanced panel data from 46 commercial banks operating in India between 2011 and 2023. Initially, we utilized the Data Envelopment Window Analysis and Malmquist Productivity Index measures to analyze the efficiency and total factor productivity index. Second, applying panel regression, we used the CAMELS framework to regress various bank and country-specific factors against Indian banks' performance indicators. The results show that the banking industry in India witnessed a consistent pattern throughout the study period. Despite this, an examination of each bank's performance at the individual level reveals that public banks consistently display the highest average efficiency score, whereas foreign banks are more productivity-advanced. The regression results suggest that Indian Banks have been significantly affected by bank, country-specific and market structure factors. Government initiatives to consolidate banks, positively affect the profitability, productivity, and efficiency of banks, and smooth resource mobilization might cushion an emerging economy such as India.
Keywords: B41; C33; C67; G21; 650; DEWA; malmquist productivity index; panel regression; CAMELS framework; commercial banks